Waste prevention in the clothing and fashion sector: innovation in the design process (ModaPalavra e-periódico, 2013)
This article presents the problem of textile waste generation in the fashion and clothing manufacturing sector and study strategies for cleaner production presenting the zero waste design process as an alternative to reducing textile waste and its application as radical innovation process compared with conventional methods of development of fashion products. The results are validated in a manufacturer company of fashion products and indicate the viability of applying the proposed study since the creation, development and production in the garment sector.
Keywords: textile waste; innovation; zero waste design